Democratic decentralisation and good governance in North-East India - Shamshad, Ahmad (2016)
The North-East is situated in a geographically vulnerable zone. A major risk associated with this unique geo-political location is that of cross-border human trafficking. Adding to the vulnerability are factors of unemployment, gender-violence, armed conflicts, and oppressive social structures. It is connected with rest of India by a narrow 27km-wide strip of land, called the 'chicken neck', in West Bengal through which natural and finished products such as oil, gas and tea go to rest of India and consumer goods, food and other items come in. Given the geographic remoteness, it is not surprising that people feel alienated and distant from rest of the country. There are special laws, constitutional provisions such as the Sixth Schedule and Article 371, which seek to protect the traditions, lands and rights of various hill communities. The sustained conflict, geographical isolation, militarisation, infiltration and migration have led to a drying up of investments, and the lack of economic and social development in the region. However, democratic decentralisation, peoples' participation in developmental activities and North-East-centric government policies have helped in bridging the gap and bringing the region into mainstream. - Reproduced.
Keywords: Decentralization - India, North East; Goog governance - India, North East; Public administration - India, North East; Public administration